Research Assessment in the Humanities Towards Criteria and Procedures - Ochsner, Michael; Hug, Sven E.; Daniel, Hans-Dieter.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book is open access, which means that you have free and unlimited access. This book analyses and discusses the recent developments for assessing research quality in the humanities and related fields in the social sciences. Research assessments in the humanities are highly controversial and the evaluation of humanities research is delicate. While citation-based research performance indicators are widely used in the natural and life sciences, quantitative measures for research performance meet strong opposition in the humanities. This volume combines the presentation of state-of-the-art projects on research assessments in the humanities by humanities scholars themselves with a description of the evaluation of humanities research in practice presented by research funders. Bibliometric issues concerning humanities research complete the exhaustive analysis of humanities research assessment. The selection of authors is well-balanced between humanities scholars, research funders, and researchers on higher education. Hence, the edited volume succeeds in painting a comprehensive picture of research evaluation in the humanities. This book is valuable to university and science policy makers, university administrators, research evaluators, bibliometricians as well as humanities scholars who seek expert knowledge in research evaluation in the humanities.
Keywords: Educational tests and measurements; Education, Higher; Ethics; Public administration; Assessment and Testing; Higher Education; Moral Philosophy and Applied Ethics; Public Administration